2012
DOI: 10.1126/science.1228211
|View full text |Cite
|
Sign up to set email alerts
|

Texture of Nanocrystalline Nickel: Probing the Lower Size Limit of Dislocation Activity

Abstract: The size of nanocrystals provides a limitation on dislocation activity and associated stress-induced deformation. Dislocation-mediated plastic deformation is expected to become inactive below a critical particle size, which has been proposed to be between 10 and 30 nanometers according to computer simulations and transmission electron microscopy analysis. However, deformation experiments at high pressure on polycrystalline nickel suggest that dislocation activity is still operative in 3-nanometer crystals. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 32 publications
8
76
0
Order By: Relevance
“…As shown in Fig. 2, the large curvatures of the 2D diffraction lines of nickel nanocrystals also provide strong evidence for the shear stress in ultrafine nickel nanocrystals (24,27). Therefore, it is excluded that the observed texture loss of platinum in ultrafine nickel media arises from the lack of shear stress.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 2, the large curvatures of the 2D diffraction lines of nickel nanocrystals also provide strong evidence for the shear stress in ultrafine nickel nanocrystals (24,27). Therefore, it is excluded that the observed texture loss of platinum in ultrafine nickel media arises from the lack of shear stress.…”
Section: Significancementioning
confidence: 86%
“…Such in situ high-pressure textural studies thus provide the means to investigate deformation mechanisms and help constrain the fundamental physics of deformation at the nanoscale. For the calculations, b p = 0.244 nm (9), G = 76 GPa (27,29), ν= 0.31 (27).…”
Section: Significancementioning
confidence: 99%
“…The combination of this two recent approaches open-up new possibilities for the use of up converting particles in many different applications: in imaging for biology of course but also for photodynamic therapy [129,130,131,132] or for photovoltaics [133].…”
Section: Up Conversion Of Photoluminescencementioning
confidence: 99%
“…In nanocrystalline metals, the grain boundarymediated process becomes dominant (24,25) but the size limit of the dislocation activation is extended to smaller grains at highpressure conditions (26). However, for the conventional materials with coarse grain sizes it is found that all dislocation-mediated deformation modes are activated irrespective of the grain size and the grain orientation plays an important role in the deformation modes (21-23, 27, 28).…”
mentioning
confidence: 99%